2022
DOI: 10.3390/ma15144982
|View full text |Cite
|
Sign up to set email alerts
|

Geotechnical Evaluation of Loess Modifications as the Sustainable Compacted Soil Liner Material in Solid Waste Landfill

Abstract: This paper studied the anti-seepage ability of the modified loess by using attapulgite, which is abundant in local areas. The possibility of using the modified loess as the sustainable compacted soil liner material in a solid waste landfill was also considered in this research. The materials were then evaluated using Nuclear Magnetic Resonance (NMR), Scanning Electron Microscopy (SEM), X-ray Diffraction (XRD), and an Impermeability Mechanism (IM). The experimental results showed that the permeability coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…Attapulgite mainly improves the soil by filling the gaps between the soil particles and increasing the internal friction of the soil. Zhang et al [ 27 ] revealed that the mechanism of attapulgite-modified loess is that attapulgite fills the pores between loess particles and forms a sheet-like integral structure with loess, thus reducing the permeability coefficient. Furthermore, Chen et al [ 28 ] revealed that attapulgite has a special crystal structure and alternating properties, which provide it with excellent ion exchange and surface adsorption properties, which can effectively improve the physical properties of soil.…”
Section: Resultsmentioning
confidence: 99%
“…Attapulgite mainly improves the soil by filling the gaps between the soil particles and increasing the internal friction of the soil. Zhang et al [ 27 ] revealed that the mechanism of attapulgite-modified loess is that attapulgite fills the pores between loess particles and forms a sheet-like integral structure with loess, thus reducing the permeability coefficient. Furthermore, Chen et al [ 28 ] revealed that attapulgite has a special crystal structure and alternating properties, which provide it with excellent ion exchange and surface adsorption properties, which can effectively improve the physical properties of soil.…”
Section: Resultsmentioning
confidence: 99%
“…It has a certain bearing capacity in the dry state, but the cementation point between the particle skeleton will dissolve when it encounters water. Zhang Zhengrui et al [3][4] conducted a study on the seepage prevention of lime-modified loess on the embankment slope of deep collapsible loess. They found that lime piles and lime seepage prevention walls have good performance as transverse seepage prevention structures, and the performance of lime pile seepage prevention walls is better than that of lime compacted piles.…”
Section: Introductionmentioning
confidence: 99%
“…However, the chemical compatibility of soil-bentonite cut-off walls with landfill leachate is poor, and its antifouling properties are easily affected by landfill leachate (most importantly, to increase the hydraulic conductivity of the cut-off walls) [6,[12][13][14][15][16][17]. Attapulgite is a clay mineral that is cheap and readily available [18,19], and it seems to be well suited for use in pollution containment barriers [20][21][22][23][24][25][26][27]; it is considered to be a viable alternative to bentonite in landfill cut-off walls [20,21,28]. Some research has experimentally confirmed the technical feasibility of using attapulgite as a landfill cut-off wall material [20,[29][30][31].…”
Section: Introductionmentioning
confidence: 99%